2009
DOI: 10.1016/j.bbamem.2009.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipid/cholesterol regulation of neurotransmitter receptor conformation and function

Abstract: Like all other monomeric or multimeric transmembrane proteins, receptors for neurotransmitters are surrounded by a shell of lipids which form an interfacial boundary between the protein and the bulk membrane. Among these lipids, cholesterol and sphingolipids have attracted much attention because of their well-known propensity to segregate into ordered platform domains commonly referred to as lipid rafts. In this review we present a critical analysis of the molecular mechanisms involved in the interaction of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
197
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 219 publications
(202 citation statements)
references
References 182 publications
4
197
0
1
Order By: Relevance
“…Several ligand-gated ion channels and G-protein coupled receptors contain specific binding sites, either in their transmembrane helices or extracellular loop structures, for cholesterol and sphingolipids, the binding of which allows conformational changes necessary for function. 10 Subtle changes in lipid species alter membrane architecture and impose constraints on lipid-protein and/or protein-protein interactions influencing the function of membrane proteins. Levels of raft-associated lipids such as sphingomyelin, ceramides, and cholesterol significantly increase with age, 11 suggesting that lipid raft densities and associated signaling process are likely subjected to age-dependent alterations that could contribute to the initiation and/or progression of AD, 9 as could dietary factors that affect lipid accumulation and metabolism and alterations in membrane lipids resulting from oxidative stress (e.g.…”
Section: Prpmentioning
confidence: 99%
“…Several ligand-gated ion channels and G-protein coupled receptors contain specific binding sites, either in their transmembrane helices or extracellular loop structures, for cholesterol and sphingolipids, the binding of which allows conformational changes necessary for function. 10 Subtle changes in lipid species alter membrane architecture and impose constraints on lipid-protein and/or protein-protein interactions influencing the function of membrane proteins. Levels of raft-associated lipids such as sphingomyelin, ceramides, and cholesterol significantly increase with age, 11 suggesting that lipid raft densities and associated signaling process are likely subjected to age-dependent alterations that could contribute to the initiation and/or progression of AD, 9 as could dietary factors that affect lipid accumulation and metabolism and alterations in membrane lipids resulting from oxidative stress (e.g.…”
Section: Prpmentioning
confidence: 99%
“…They are major components of membrane microdomains known as "lipid rafts" (22) and are important players in cell signaling (23) and cell-cell interaction (24). By influencing membrane properties and/or by direct interaction with membrane proteins, gangliosides modulate the activity of many tyrosine kinase (25)(26)(27)(28) and neurotransmitter receptors (29), ion channels (30,31), and downstream cell signaling pathways. In addition, gangliosides regulate axon-myelin communication and the maintenance of myelinated axons in the adult central and peripheral nervous systems (32)(33)(34).…”
mentioning
confidence: 99%
“…The bifacial geometry of cholesterol appears to be the outcome of this struggle [48]. The dissymmetrical nature of the molecule is manifested in the contrast between the rough β face, with methyl substituents in C10 and C13 and an iso-octyl chain in C17, with the featureless, smooth α face.…”
Section: Possible Raisons D'être For Cholesterol Induction Of Orderedmentioning
confidence: 99%
“…Comparative analyses of the energy of interaction of cholesterol with pLGIC, GPCRs and various other membrane proteins revealed that the CARC motif generally exhibits higher affinity for cholesterol than the CRAC motif [49]. Essentially two explanations lie at the root of the difference in the predictive value of the CRAC and CARC linear algorithms: the snorkeling effect of Lys/Arg residues, which places the polar residues exposed to the aqueous milieu and the hydrophobic residues buried in the bilayer hydrophobic core [128] on the one hand and the structure of cholesterol itself [48], as reviewed in [46,49] on the other.…”
Section: Identifying Cholesterol-recognition Motifs In Membrane Proteinsmentioning
confidence: 99%
See 1 more Smart Citation